On pointwise convergence of bivariate nonlinear singular integral operators - Gumrah Uysal; Mine M. Yilmaz; Ertan Ibikli (Kuwait Journal of Science)
In this paper, we present some theorems on pointwise convergence and the rate of pointwise convergence for the family of nonlinear bivariate singular integral operators of the following form: